Higher Education Students' Perceptions and Attitudes about Using ChatGPT in Oman: A Case Study of OCMT (The International Journal of Educational Sciences and Arts, 2024)
This study aims to determine the role of ChatGPT as a virtual assistant for the students in higher education institutions in the Sultanate of Oman to enhance learning, foster their skill growth and improve their productivity. It also aims to identify how the students at Oman College of Management and Technology (OCMT) can use ChatGPT in an effective way, the advantages of using it, and the challenges that prevent it from being used in education, from their point of view, keeping in mind the ethical considerations that arise in the process. Some consider it as a support for the process of developing education, while others see it as a threat that affects its future. On the positive side, ChatGPT helps improve education, while on the negative side, it raises several concerns about fraud and plagiarism. Since the results of the survey showed that many students at Oman College of Management and Technology tend to use AI applications in their studies, the problem of this study emerged in the researchers' desire to explore the degree of students' use of ChatGPT, the advantages of using it, the obstacles, challenges and ethical considerations that may affect its integration in education.
Keywords: ChatGPT; Oman College of Management and Technology; AI; Education, Learning